Opioid-Prescribing Practices Between Total Knee and Hip Arthroplasty in an Outpatient Versus Inpatient Setting. Issue 2 (5th March 2022) - Nouraee, Cyrus M.; McGaver, Rebecca Stone; Schaefer, Jacob J.; O'Neill, Owen R.; Anseth, Scott D.; Lehman-Lane, Justina; Uzlik, Rachel M.; Giveans, M. Russell
ABSTRACT: Despite trends showing increases in the utilization of outpatient (OP) ambulatory surgery centers (ASCs) and decreases in the utilization of inpatient (IP) facilities for total knee arthroplasty (TKA) and total hip arthroplasty (THA), little is known about opioid prescribing for these procedures between each setting. This study evaluated differences in opioid prescribing and consumption between OP ASC and IP settings for elective TKA and THA surgeries over a 1-year period. Data collection also included pain and satisfaction of pain control postsurgery. In an OP ASC, analysis revealed a significant decrease in pills prescribed ( p < .001, p < .001) and consumed ( p < .001, p < .001) for TKA and THA, respectively. There was a significant decrease in the morphine equivalence units prescribed ( p < .001, p < .001) and consumed ( p < .001, p < .001) for TKA and THA, respectively. For TKA, pain was significantly lower ( p = .018) and satisfaction of pain control was significantly higher ( p = .007). For THA, pain ( p = .374) and satisfaction of pain control ( p = .173) were similar between the settings. Benefits of performing these surgeries in an OP ASC setting are patients having similar or lower levels of pain and having similar or higher satisfaction of pain control. Patients are also prescribed and consume less opioids. This has important implications for healthcare systems.